Frequency of pressure fluctuations in the stilling basin for the spillway of raised Gross Dam, Colorado - Tasdelen, Selina, author; Ettema, Robert, advisor; Thornton, Christopher, advisor; Little, Ann M., committee member (Colorado State University. Libraries, 2021)
Gross Dam, Colorado, was constructed in 1954 to provide potable water to the city of Denver, Colorado. The location of Gross Dam is in Boulder County, Colorado. The dam itself is a high, curved concrete gravity-arch dam that retains Gross Reservoir, a reservoir capacity that of volume 51,573, 109.1 cubic meter. The Gross Reservoir Expansion (GRE) Project will increase the height of the Gross Dam from 39.93 m to an ultimate height of 143.56 m by 2025, thereby creating more storage behind the Gross Dam. The new stepped spillway required for GRE will be the highest stepped spillway in the U.S. Besides the height of the spillway, the steepness, the length, and the curved form of the chute will make the spillway stand out. This study focused on (1) determining how roller-rotation frequency varied with water discharge for the full range of the discharges expected for the spillway, (2) determining the main frequencies in the pressure fluctuations at selected locations along the stilling basin, and (3) relating frequency fluctuations of measured pressure to frequencies of features evident in the flow field too and through the stilling basin. This effort involved assessing the influence of flow discharge on the rotation frequency of a major roller formed immediately upstream of the row of baffle blocks for each discharge. The experimental investigation carried out at the Hydraulics Laboratory of Colorado State University, Engineering Research Center, for the current Gross Dam. The frequency of the rotation of the roller formed immediately upstream of the row of the baffle blocks determined approximately from the observation for every flow rate. The mean value of the rotation frequency of the roller formed for the PMF-equivalent discharge down the hydraulic model of the spillway (0.348 m3/s) was 2.45 Hz or 0.5 Hz at prototype scale. The plot of the roller-rotation frequency versus discharge showed that there was a proportional relationship between the rotation frequency and the discharge. The dynamic pressures were measured with the use of four pressure sensors which were positioned in front of the floor, behind the floor, at the face of the baffle block, and the behind the baffle block. The sampling rate of these sensors was 2,500 Hz. The maximum pressure (prototype scale) recorded at the front face of the baffle block when the model-scale flowrate was equivalent to the 1.0 PMF was 59.78 kPa. Low-pass filter applied to the original signal of pressures, and the pressure signal was filtered out at frequencies above 200 Hz (model scale). The cut off frequency of the filtered signal was chosen 200 Hz, as flow oscillations would not occur at this frequency. Then, Fast Fourier Transform (FFT) method was applied to both original and filtered signal. The result showed that filtered FFT gave about the same result as the FFT from the unfiltered data and there was no continuous low frequency or continuous high frequency pattern, indicating that the pressure signals oscillated irregularly, as did the roller formed in the front of the stilling basin. Therefore, FFT could not find the dominant frequency in the signal. The largest peak frequencies at prototype scale for the upstream floor, front face of the baffle block, downstream face of the baffle block, and downstream floor of the stilling basin were 0.496, 1.15, 1.396, and 1.544 Hz, respectively.
Keywords: FFT; pressure frequencies; baffle block; stilling basin; fluctuations